2020
DOI: 10.3390/ijerph17176127
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Built Environment and the Neighborhood in Promoting the Physical Activity and the Healthy Aging in Older People: An Umbrella Review

Abstract: (1) Background: The aim of this study is to establish which specific elements of the built environment can contribute to improving the physical activity of self-sufficient, noninstitutionalized and living in the city adults > 65 years. (2) Methods: An extensive literature search was conducted in several database. Umbrella review methodology was used to include the reviews that presented a sufficient methodological quality. (3) Results: Eleven reviews were included. The elements positively associated with ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
69
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 38 publications
11
69
5
1
Order By: Relevance
“…Sun et al found that a lower residential density would motivate women adults to spend more time in RW. However, the finding of this study was in conflict with numerous previous studies [ 34 , 36 , 48 , 49 , 50 , 51 , 52 ]. Besides, previous studies from our team [ 29 , 30 ] also observed a positive association between residential density and RPA.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Sun et al found that a lower residential density would motivate women adults to spend more time in RW. However, the finding of this study was in conflict with numerous previous studies [ 34 , 36 , 48 , 49 , 50 , 51 , 52 ]. Besides, previous studies from our team [ 29 , 30 ] also observed a positive association between residential density and RPA.…”
Section: Discussioncontrasting
confidence: 99%
“…The results suggested that a good street connectivity would motivate older people to engage more in RW and RPA. This finding is consistent with previous studies [ 31 , 47 , 49 , 58 , 59 ]. In a recently published umbrella review study, Bonaccorsi et al showed strong evidence supporting the idea that street connectivity was positively associated with older people’s physical activity [ 49 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Access to services was negatively associated with elderly LTPA in Hangzhou. This finding was not in line with previous studies [ 48 , 49 ]. Van et al suggested that perceived short distances to services was significantly positively related to elderly walking/cycling behaviors in Belgium [ 49 ].…”
Section: Discussioncontrasting
confidence: 96%
“…The present study found that higher LUM was associated with greater prevalence of diabetes in adults aged 60 or over. Previous studies have supported that high-level LUM encourages participation in physical activity due to better access to local destinations that help reduce obesity and diabetes [ 33 , 34 , 35 ]. The elderly, who are more sensitive to stress from their residence environments, might be exposed to higher levels of stresses when living in areas with mixed residential, commercial, and industrial land-use, usually located in urban centers [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%